Development of Problem Solving Based E-LKPD on Acid and Base Materials to Train Students’ Critical Thinking - Fadliilah, Octavia Dwi; Nasrudin, Harun (Universitas Lampung, 2023)
Development of Problem Solving Based E-LKPD on Acid and Base Materials to Train Students' Critical Thinking Skills. This study aims to describe the validity, practicality, and effectiveness of problem solving-based e-LKPD on acid and base materials to train students' critical thinking skills. The method used uses the development model by Thiagarajan, Semmel, and Semmel with restrictions only on the third stage, namely (1) Define Stage, (2) Design Stage, (3) Development Stage, (4) Disseminate Stage. The research was conducted at SMAN Jogoroto Jombang with the research subject of class XI students who had insufficient critical thinking skills. The data analysis technique used is to determine the mode of validation results, calculate the percentage of student response questionnaire sheets, calculate the percentage of student activity observation sheets, and through the calculation of N-gain scores. The results of this study indicate that 1) content validity gets a mode number 5 with a very good category, 2) the average learner response questionnaire is 95% practical category, 3) the relevant activity of students is 93.32% and 96.65% practical category, 4) the average N-gain is 0.91 in the high category. Based on the results of the study, it can be concluded that the developed e-LKPD is feasible to use because it meets the criteria of validity, practicality, and effectiveness.Keywords: e-LKPD, Problem Solving, Critical Thinking Skills, Acids and Bases. DOI: 10.23960/jppk.v12.i3.2023.01